Impact of Digital Marketing Strategy on Tourism Industry: Revolutionizing the Travel Experience through Digital Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Use of Internet reaching out to target travelers have evolved. Digital marketing has an crucial part of every business. The increasing role of digital marketing has pretentious the mode businesses encourage their offerings to existing as well as new travelers. The need for digital marketing has been felt like never before in the tourism industry. Travelers have instant access to all kinds of information on the latest offers and best prices. Digitally connected touch points of a customer journey for seamless travel Digitization influences digital enterprise architectures and systems arrangement of business model and digital technologies Outsourcing Flexibility, agility and integration of mobile devices.